Lithium ion battery negative electrode material and preparation method thereof, lithium ion battery negative electrode pole piece and lithium ion battery

By using carbon-I and carbon-II with specific structural ratios and graphitization in lithium-ion batteries, combined with ball milling and carbonization treatment of scale graphite and hard carbon precursors, the capacity of lithium-ion battery anode materials and Kulun are solved. The shortcomings in efficiency and rate performance have achieved efficient battery performance improvement.

CN119170800APending Publication Date: 2024-12-20CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410995988.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have poor performance in capacity, first-week Coulomb efficiency and rate performance, and are difficult to meet the requirements of the new energy industry for high energy density, long cycle performance and excellent rate performance.

Method used

Using a negative electrode material including carbon-I and amorphous structures of carbon-II, by controlling the weight ratio of carbon-I and carbon-II and the graphitization degree of carbon-II, combined with scale graphite and hard carbon Ball milling and carbonizing treatment of the precursor, a negative electrode material with excellent performance was prepared.

Benefits of technology

It improves the capacity of lithium-ion batteries, first-week Coulomb efficiency and rate performance, simplifies the preparation process, reduces costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170800A_ABST
    Figure CN119170800A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a lithium ion battery negative electrode material and a preparation method thereof, a lithium ion battery negative electrode plate and a lithium ion battery. The negative electrode material comprises carbon-I with a crystalline structure and carbon-II with an amorphous structure; wherein the weight ratio of the carbon-I to the carbon-II is 1: (0.6-20); in the negative electrode material, the graphitization degree of the carbon-II is 1-2. According to the present invention, the carbon-I having the crystalline structure and the carbon-II having the amorphous structure are adopted, the long-range ordered carbon-I and the short-range ordered carbon-II are compounded, and the weight ratio of the carbon-I to the carbon-II and the graphitization degree of the carbon-II are controlled so as to easily improve the lithium ion diffusion rate; and the crystalline degree of the hard carbon precursor in the high-temperature carbonization process is improved due to the existence of the crystalline flake graphite, the carbon-I is uniformly distributed between the carbon-II, and defect sites on the surface of the carbon-II are reduced, so that the lithium ion battery containing the negative electrode material has excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery negative electrode material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery. Background Art

[0002] Since the 21st century, fossil energy such as coal and oil has been decreasing, and the use of large amounts of fossil energy has led to increasingly prominent environmental problems such as the greenhouse effect. The development of the new energy industry is an inevitable trend. Among them, lithium-ion batteries have the advantages of high energy density, safety and environmental protection, and have broad development prospects in the fields of electric vehicles and energy storage.

[0003] The negative electrode of lithium-ion batteries is usually flake graphite, which has high conductivity and stability and occupies the vast majority of the market in the field of lithium-ion batteries. However, due to the small interlayer spacing and insufficient sodium storage sites of the graphite negative electrode, its specific capacity is low and its high-power performance is poor, which makes it difficult to meet the future new energy industry's requirements for high energy density, long cycle performance, and excellent rate performance.

[0004] Hard carbon negative electrode is usually obtained by dehydrogenation, deoxygenation and carbonization of biomass precursors, asphalt, resin and other materials under high temperature inert atmosphere. It has many lithium storage sites and excellent rate performance. It is a very promising negative electrode material for lithium-ion batteries. However, due to its low degree of graphitization, many defects, and many side reactions with the electrolyte, it leads to low coulombic efficiency and poor cycle performance.

[0005] CN116477615A discloses a high-rate graphite negative electrode material and a preparation method thereof, the method comprising the following steps: spheroidization: spheroidizing natural flake graphite to prepare spherical graphite with a particle size of D50=5-10μm; granulation: mixing and stirring the spherical graphite and a carbon source, coating the surface to obtain a coating; carbonization: heating the coating to 1200-1350°C, carbonizing for 5.5-6h to obtain a negative electrode material; the mass ratio of the carbon source to the spherical graphite is 0.1-0.15:1, and the carbon source is a mixture of asphalt and hard carbon resin or modified asphalt. The high-rate graphite negative electrode material has the advantages of uniform carbon source coating on graphite, high rate of negative electrode material, and excellent discharge capacity and cycle performance. However, this method first spheroidizes the flake graphite, and then coats the carbon source on the surface of the graphite particles through a multi-step high-temperature carbonization process to form a pyrolytic carbon layer coated on the graphite surface to obtain a graphite negative electrode material. The preparation process is long and the energy consumption is relatively high. In addition, the structure of the obtained graphite negative electrode material is a pyrolytic carbon layer coated on the graphite surface, and the first discharge capacity is small.

[0006] Therefore, there is an urgent need to develop a lithium-ion battery negative electrode material and a preparation method thereof, a lithium-ion battery negative electrode plate and a lithium-ion battery, so that the lithium-ion battery has excellent performance in terms of capacity, first-cycle coulomb efficiency and rate performance. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of low capacity, coulombic efficiency and poor rate performance of lithium battery negative electrode materials in the prior art, and to provide a lithium ion battery negative electrode material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises: carbon-I having a crystalline structure and carbon-II having an amorphous structure;

[0009] Wherein, the weight ratio of carbon-Ⅰ to carbon-Ⅱ is 1:(0.6-20);

[0010] In the negative electrode material, the graphitization degree of the carbon-II is 1-2.

[0011] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises:

[0012] The flake graphite and the hard carbon precursor are ball-milled and then carbonized to obtain a negative electrode material;

[0013] Wherein, the mass ratio of the flake graphite to the hard carbon precursor is 1:(3-100).

[0014] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0015] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0016] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0017] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:

[0018] (1) The negative electrode material provided by the present invention comprises: carbon-I having a crystalline structure and carbon-II having an amorphous structure. Due to the combination of long-range ordered carbon-I and short-range ordered carbon-II, and by controlling the weight ratio of carbon-I to carbon-II and the graphitization degree of carbon-II, the lithium ion diffusion rate is improved. The presence of flake graphite improves the degree of crystallization during the high-temperature carbonization process of the hard carbon precursor, and makes carbon-I evenly distributed among carbon-II, reducing the defect sites on the surface of carbon-II, so that the lithium ion battery containing the negative electrode material has excellent capacity, first-cycle coulomb efficiency and rate performance.

[0019] 2) The method for preparing the negative electrode material provided by the present invention controls the amount of flake graphite and hard carbon precursor, thereby affecting the structure and performance of the negative electrode material. The preparation method is simple and safe, low in cost, and has good continuity, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a SEM image of the negative electrode material obtained in Example 1;

[0021] Figure 2 This is the XRD pattern of the negative electrode material obtained in Example 1. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] The first aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises: carbon-I having a crystalline structure and carbon-II having an amorphous structure;

[0024] Wherein, the weight ratio of carbon-Ⅰ to carbon-Ⅱ is 1:(0.6-20);

[0025] In the negative electrode material, the graphitization degree of the carbon-II is 1-2.

[0026] In the present invention, when the weight ratio of carbon-Ⅰ to carbon-Ⅱ satisfies the above range, carbon-Ⅰ can regulate the degree of graphitization of hard carbon, and carbon-Ⅰ is evenly dispersed in the middle of carbon-Ⅱ, reducing the defect sites on the surface of carbon-Ⅱ, which is beneficial for the battery to achieve high capacity, first-cycle coulombic efficiency and rate performance.

[0027] In the present invention, when the graphitization degree of carbon-II in the negative electrode material meets the above range, when the graphitization degree is less than 1, there are many defects on the surface of carbon-II, which will react with the electrolyte, which is not conducive to the battery to achieve high coulombic efficiency; when the graphitization degree is greater than 2, it will cause the microcrystalline layer spacing to be smaller, which is not conducive to the diffusion of lithium ions in the negative electrode material; when it is in the above range, carbon-I is evenly dispersed in the middle of carbon-II, reducing the defect sites on the surface of carbon-II, which is conducive to the battery to achieve high capacity, first-week coulombic efficiency and rate performance.

[0028] Furthermore, the weight ratio of carbon-Ⅰ to carbon-Ⅱ is 1:(1-10).

[0029] Furthermore, the graphitization degree of carbon-II in the negative electrode material is 1-1.5.

[0030] According to the present invention, the carbon-I is prepared by carbonizing flake graphite; the carbon-II is prepared by carbonizing a hard carbon precursor, and the hard carbon precursor is selected from at least one of cellulose, lignin, starch, polyvinyl pyrrolidone, polyacrylonitrile and chitosan; the hard carbon precursors are all commercially available, for example, cellulose is commercially available from Shanghai McLean Biochemical Technology Co., Ltd., lignin is commercially available from Shanghai McLean Biochemical Technology Co., Ltd., and starch is commercially available from Shanghai McLean Biochemical Technology Co., Ltd.

[0031] According to the present invention, in the XRD spectrum of the negative electrode material, the half-peak widths of the diffraction peaks at 2θ of 26.4° and 54.6° are between 0.1° and 0.5°.

[0032] According to the present invention, in the XRD spectrum of the negative electrode material, the half-peak widths of the diffraction peaks at 2θ of 22°-25° and 42°-44° are between 0.8° and 5°.

[0033] In the present invention, the half-peak width, i.e., the peak width at half the height of the diffraction peak, is the distance between the two points where a straight line parallel to the bottom of the peak is drawn through the midpoint of the peak height and intersects the two sides of the peak. In the XRD spectrum of the negative electrode material, a diffraction peak appears in the above 2θ, and in the negative electrode material, carbon-Ⅰ has a crystalline structure, carbon-Ⅱ has an amorphous structure, and carbon-Ⅰ is evenly distributed between carbon-Ⅱ, which can reduce defects on the surface of carbon-Ⅱ, and is conducive to the battery to achieve high capacity, first-cycle coulomb efficiency and rate performance.

[0034] In a preferred embodiment of the present invention, the negative electrode material comprises: carbon-I having a crystalline structure and carbon-II having an amorphous structure;

[0035] Wherein, the weight ratio of carbon-Ⅰ to carbon-Ⅱ is 1:(2-8);

[0036] In the negative electrode material, the graphitization degree of the carbon-II is 1.2-1.4.

[0037] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises:

[0038] The flake graphite and the hard carbon precursor are ball-milled and then carbonized to obtain a negative electrode material;

[0039] Wherein, the mass ratio of the flake graphite to the hard carbon precursor is 1:(3-100).

[0040] Among them, the dosage relationship between the flake graphite and the hard carbon precursor makes the flake graphite evenly distributed in the hard carbon precursor, and at the same time fully induces the structural ordering of the hard carbon precursor during the carbonization process, which is beneficial to the battery to achieve high capacity, first-cycle coulombic efficiency and rate performance.

[0041] According to the present invention, the mass ratio of the flake graphite to the hard carbon precursor is 1:(5-50).

[0042] In the present invention, when the mass ratio of the flake graphite to the hard carbon precursor satisfies the above range, the flake graphite is evenly dispersed in the middle of the hard carbon precursor after ball milling and mixing, and it is beneficial for the hard carbon material to have a suitable degree of graphitization, thereby improving the first-cycle coulomb efficiency of the negative electrode material and the diffusion efficiency of lithium ions.

[0043] According to the present invention, the ball milling conditions include: the diameter of the ball for ball milling is 5-10mm, preferably 6-8mm; the ball-to-material mass ratio is (1-20):1, preferably (5-10):1; the ball milling speed is 50-800rpm, preferably 100-500rpm; the time is 0.5-5h, preferably 1-3h.

[0044] In the present invention, when the ball milling conditions meet the above range, sufficient mixing of the flake graphite and the hard carbon precursor is ensured, while the structures of the flake graphite and the hard carbon precursor themselves can be prevented from being destroyed.

[0045] According to the present invention, the carbonization conditions include: under protective gas, heating from room temperature to 500-1100°C at a heating rate of 2-10°C / min for 1-5 hours. Room temperature is 25-35°C.

[0046] According to the present invention, the carbonization conditions include: under protective gas, heating from room temperature to 700-900° C. at a heating rate of 3-5° C. / min for 1-3 hours.

[0047] In the present invention, when the carbonization conditions meet the above range, it can ensure that the hard carbon precursor can be fully carbonized, so that the microcrystalline structure of the hard carbon precursor can be appropriately developed.

[0048] According to the present invention, the protective gas is selected from argon and / or nitrogen.

[0049] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0050] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0051] According to the present invention, a method for preparing a negative electrode sheet of a lithium ion battery comprises the following steps:

[0052] The negative electrode material, conductive agent Super P and lithium polyacrylate were weighed and mixed into a slurry in a mass ratio of 8:1:1, coated on a copper foil, vacuum dried and rolled to form a negative electrode sheet for a lithium-ion battery.

[0053] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0054] According to the present invention, a method for preparing a lithium ion battery comprises the following steps:

[0055] A lithium-ion battery negative electrode sheet including a negative electrode material is used, a metal lithium sheet is used as the positive electrode, a Celgard2500 separator, and an electrolyte is a 1M LiPF6 mixed solution of EC, DMC and EMC (wherein the volume ratio of EC, DMC and EMC is 1:1:1), and button batteries are assembled in an argon atmosphere glove box.

[0056] The present invention will be described in detail below by way of examples. In the following examples,

[0057] The capacity, first-cycle coulombic efficiency and rate performance were tested using the LAND test system (CT2001A LAND);

[0058] Polyvinyl pyrrolidone was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., model K30;

[0059] Polyacrylonitrile was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., model number P876032;

[0060] Cellulose was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0061] Lignin was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0062] Starch was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0063] Morphology test: obtained by using Hitachi's Regulus8100 scanning electron microscope;

[0064] XRD: obtained by X'Pert Pro MPD test from Nalytical;

[0065] The raw materials used in the examples and comparative examples are all commercially available.

[0066] Example 1

[0067] A mixture of flake graphite and cellulose in a mass ratio of 1:50 was ball-milled at a ball diameter of 7 mm, a ball-to-material mass ratio of 8:1, g:g, a ball-milling speed of 300 rpm, and a time of 2 h, and then carbonized at a heating rate of 4°C / min from 30°C to 800°C for 2 h under argon protective gas to obtain negative electrode material A1;

[0068] Among them, the negative electrode material A1 was tested by scanning electron microscope (SEM), and the results were as follows Figure 1 ,Depend on Figure 1 It can be seen that the negative electrode material is obtained by carbonizing flake graphite and cellulose, in which the carbon-Ⅰ obtained by carbonizing flake graphite is evenly distributed among the carbon-Ⅱ obtained by carbonizing cellulose, and it is not a coating structure.

[0069] The negative electrode material A1 was subjected to X-ray diffraction (XRD) test, and the results were as follows Figure 2 ,Depend on Figure 2 It can be seen that the half-peak widths of the diffraction peaks at 26.4° and 54.6 are 0.42° and 0.45°, respectively, representing carbon-Ⅰ with higher crystallinity, and the half-peak widths of the diffraction peaks at 22-25° and 42-44° are 2.9° and 3.2°, respectively, representing carbon-Ⅱ with lower crystallinity.

[0070] Example 2

[0071] A mixture of flake graphite and lignin in a mass ratio of 1:30 was ball-milled with a ball diameter of 8 mm, a ball-to-material mass ratio of 10:1, g:g, a ball mill speed of 500 rpm, and a time of 1 h. Then, under nitrogen protective gas, the temperature was increased from 35°C to 900°C at a heating rate of 5°C / min for 1 h to obtain negative electrode material A2.

[0072] Example 3

[0073] A mixture of flake graphite and starch in a mass ratio of 1:5 was ball-milled with a ball diameter of 6 mm, a ball-to-material mass ratio of 5:1, g:g, a ball mill speed of 100 rpm, and a time of 3 h. Then, under argon protective gas, the temperature was increased from 25°C to 700°C at a heating rate of 3°C / min for 3 h to obtain negative electrode material A3.

[0074] Comparative Example 1

[0075] The negative electrode material was prepared according to the method of Example 1, except that the mass ratio of flake graphite to cellulose was 1:1, and negative electrode material D1 was obtained.

[0076] Test Example 1

[0077] The physical properties of the negative electrode materials in the above embodiments and comparative examples were tested.

[0078] The weight of carbon-Ⅰ and carbon-Ⅱ of negative electrode materials was measured by thermogravimetric analyzer (TGA / DSC 3 + ) for testing;

[0079] The graphitization degree of the negative electrode material is calculated using the following specific steps: The graphitization degree is obtained by analyzing the Raman spectrum test data. -1 The D peak at 1580 cm represents the disordered structure of the carbon material, such as the defects of the lattice. -1 The G peak at represents the ordered structure of the carbon material lattice, and the ratio of the peak intensity of the G peak to the D peak Ig / Id represents the graphitization degree of the carbon material;

[0080] The results are shown in Table 1.

[0081] Table 1 Negative electrode material characteristic test results

[0082]

[0083]

[0084] Test Example 2

[0085] The negative electrode materials (A1-A3 and D1) prepared in Examples 1-3 and Comparative Example 1 were subjected to electrochemical performance tests.

[0086] Assembling Li-ion Batteries:

[0087] (1) Weighing negative electrode materials (A1-A3 and D1), conductive agent Super P and lithium polyacrylate in a mass ratio of 8:1:1 respectively to prepare a slurry, coating it on a copper foil, vacuum drying it, and rolling it to prepare a negative electrode sheet for a lithium-ion battery;

[0088] (2) A lithium-ion battery negative electrode sheet including a negative electrode material was used, a metal lithium sheet was used as the positive electrode, Ceglard 2500 was used as the separator, and a 1M LiPF6 mixed solution of EC, DMC and EMC (wherein the volume ratio of EC, DMC and EMC was 1:1:1) was used to assemble button cells (A1-A3 and D1) in an argon atmosphere glove box.

[0089] The constant current charge and discharge test of the battery is carried out using the blue power test system (CT2001A LAND) instrument. The test method is as follows:

[0090] After the battery was left to rest for 12 hours, it was cycled at a rate of 0.1C, with a test voltage range of 0.01V-2.5V and a current density of 1C defined as 372mA / g. The rate performance test was first activated with a current of 0.1C for 3 weeks, and then the charge and discharge test was performed with a current of 1C.

[0091] Table 2 Electrochemical performance test results

[0092]

[0093] It can be seen from Table 1-2 that the lithium ion battery negative electrode materials prepared in Examples 1-3 of the present invention have a suitable degree of graphitization and a weight ratio of carbon-I to carbon-II, achieving excellent first-cycle capacity, first-cycle coulombic efficiency and rate performance.

[0094] Compared with Comparative Example 1, in Example 1, the mass ratio of flake graphite to cellulose is 1:1, and the mass ratio of the two is too low, so that the weight ratio of carbon-I to carbon-II and the degree of graphitization of carbon-II in the lithium ion battery negative electrode material prepared in Comparative Example 1 are not within the protection scope of the present application, resulting in carbon-I not being evenly distributed in carbon-II, and the defect sites on the surface of carbon-II not being reduced, so that the prepared lithium ion battery has poor first-week capacity, first-week coulomb efficiency and rate performance.

[0095] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material includes: carbon-I with a crystalline structure and carbon-II with an amorphous structure; Wherein, the weight ratio of carbon-Ⅰ to carbon-Ⅱ is 1:(0.6-20); In the negative electrode material, the graphitization degree of the carbon-II is 1-2.

2. The negative electrode material according to claim 1, wherein In the XRD spectrum of the negative electrode material, the half-peak widths of the diffraction peaks at 2θ of 26.4° and 54.6° are between 0.1° and 0.5°.

3. The negative electrode material according to claim 1 or 2, wherein In the XRD spectrum of the negative electrode material, the half-peak widths of the diffraction peaks at 2θ of 22°-25° and 42°-44° are between 0.8° and 5°.

4. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises: The flake graphite and the hard carbon precursor are ball-milled and then carbonized to obtain a negative electrode material; Wherein, the mass ratio of the flake graphite to the hard carbon precursor is 1:(3-100).

5. The preparation method according to claim 4, wherein The mass ratio of the flake graphite to the hard carbon precursor is 1:(5-50).

6. The preparation method according to claim 4 or 5, wherein: The hard carbon precursor is selected from at least one of cellulose, lignin, starch, polyvinyl pyrrolidone, polyacrylonitrile and chitosan.

7. The preparation method according to any one of claims 4 to 6, wherein: The ball milling conditions include: the diameter of the ball for ball milling is 5-10 mm, preferably 6-8 mm; the ball-to-material mass ratio is (1-20):1, preferably (5-10):1; the ball milling speed is 50-800 rpm, preferably 100-500 rpm; the time is 0.5-5 h, preferably 1-3 h; And / or, the carbonization conditions include: under protective gas, heating from room temperature to 500-1100° C. at a heating rate of 2-10° C. / min for 0.5-5 h; Preferably, the carbonization conditions include: under protective gas, heating from room temperature to 700-900° C. at a heating rate of 3-5° C. / min for 1-3 h; More preferably, the protective gas is selected from argon and / or nitrogen.

8. A negative electrode material obtained by the preparation method according to any one of claims 4 to 7.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate of the lithium-ion battery comprises the negative electrode material described in any one of claims 1 to 3 and 8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery negative electrode sheet according to claim 9.